HUBUNGAN PERSEPSI SISWA TENTANG PENUGASAN DAN MINAT SISWA TERHADAP HASIL BELAJAR GEOGRAFI SMA NEGERI 1 RANTAU TAHUN PELAJARAN 2013/2014 - Moch Ardi Yannor (Universitas Lambung Mangkurat, 2014)
The assigment is made for students could learn to practice. This research aims to find out the correlation between the students’ perception toward assignment and students’ interest to learn Geography, between the students’ perception toward assignment and students’ achievment to learn Geography, between the students’ interest toward assignment and students’ achievment to learn Geography, between the students’ perception partially toward assignment and students’ interest toward students’ achievment to learn Geography. This research is based on quanitative approach, using random sampling in which X and XI IPS are taken as the sample. The research result states that there is correlation between the students’ perception and assignment in which the correlation score 0,666 wiht the significance of sig. 0,000 < 0,05, there is no significant correlation between the students’ perception toward assignment and students’achievment toward learning Geography in which it says 0,056 with the signifance of sig. 0,523 > 0,05, there is no correlation between the students’ interest toward assignment and students’ achievment toward learning Geography in which it says 0,001 with the significance of sig. 0,991 > 0,05, and it is the most dominant factor based on partial correlation, namely 0,667 with the significance of 0,000 < 0,05, so Ho is refused.Key Words: students’ perception, assignment, interest, achievment, and Geography